Application of CO2 carbon stable isotope analysis to ant trophic ecology. Issue 12 (29th October 2020) - Balzani, Paride; Venturi, Stefania; Muzzicato, Daniela; Tassi, Franco; Vaselli, Orlando; Frizzi, Filippo; Frasconi Wendt, Clara; Nisi, Barbara; Masoni, Alberto; Santini, Giacomo
Abstract: Stable isotope analysis of animal tissues is commonly used to infer diet and trophic position. However, it requires destructive sampling. The analysis of carbon isotopes from exhaled CO2 is non‐invasive and can provide useful ecological information because isotopic CO2 signatures can reflect the diet and metabolism of an animal. However, this methodology has rarely been used on invertebrates and never on social insects. Here, we first tested whether this method reflects differences in δ 13 C‐CO2 between workers of the Mediterranean ant Crematogaster scutellaris (Olivier) (Hymenoptera: Formicidae, Crematogastrini) fed with sugar from beet (C3; Beta vulgaris L., Amaranthaceae) or cane (C4; Saccharum officinarum L., Poaceae). We found that a significant difference can be obtained after 24 h. Consequently, we used this technique on wild co‐occurring ant species with different feeding preferences to assess their reliance on C3 or C4 sources. For this purpose, we sampled workers of C. scutellaris, the invasive garden ant Lasius neglectus (van Loon et al.) (Lasiini), and the harvester ant Messor capitatus (Latreille) (Stenammini). No significant differences in their carbon isotopic signatures were recorded, suggesting that in our study site no niche partitioning occurs based on the carbon pathway, with all species sharing similar resources. However, further analysis revealed that M. capitatus, a seed‐eating ant, can be regarded as a C3 specialist, whereas L. neglectus and C. scutellaris are generalists that rely on both C3 and C4 pathways, though with a preference for the former. Our results show that this methodology can be applied even to small animals such as ants and can provide useful information on the diets of generalist omnivores. Abstract : We tested the applicability of CO2 stable isotope analysis to detect differences in diet use of the model ant species Crematogaster scutellaris (Hymenoptera: Formicidae) in the laboratory. Consequently, we compared the isotopic signatures of CO2 produced by colonies of co‐occurring ants with different feeding preferences ( C. scutellaris, Lasius neglectus, Messor capitatus ). No significant differences were found; however, the seed‐eating ant M. capitatus appeared to be a C3 specialist, whereas the other two species relied on both C3 and C4 pathways.